The timing of the passing of property and risk under the English Sale of Goods Act 1979, the CISG and the Libyan law: the interplay between the principle of party autonomy and the default rule - Aboukdir, Anwar (University of Stirling, 2016)
This thesis attempts to critically and comparatively analyse the issues relating to the passing of property and risk under the United Nations Convention on the Contract for International Sale of Goods (CISG) and English Law (SGA). The passing of property and risk plays a central role in the area of international legislation in relation to sales contracts. These elements can be the most significant components in contracts of sale between parties, whether in the international or domestic field. The reason is founded on their legal nature and the close relationship between them. The passing of property and risk has been a central issue for practitioners, judges and lawyers dating back to the Roman period and several ideas have been proposed to resolve it. Where the situation is different for contracts of sale in relation to the passing of property and risk, whether in the domestic or international field, it still creates many unresolved problems, because of ongoing changes in the field of modern commerce, which may contribute to unfair implications between the parties. It has been observed in this thesis that both English law and the CISG adopt the party autonomy principle, where the intention of the parties - whether in relation to the passing of property or risk - is the basic rule. However, the difference lies in the default rules. While English law involves default substitutional rules, which apply in cases where there is an absence of an expressed or implied indication regarding the intention between the parties, the CISG lacks such default rules regarding the transfer of property, which could be viewed as its main weakness, although the CISG does involve such provisions with respect to the transfer of risk. This thesis willdiscusses, the legal nature of the rules in relation to the passing of property and risk, and the role of the party autonomy principle, and the impacts and legal difficulties that might arise through the application of these rules, whether they are default rules or based on the party autonomy principle. It will also examine the legal gaps and weaknesses of both legal systems in an attempt to identify such legal difficulties and to find appropriate solutions and remedies.